Efektivitas Edukasi Kesehatan Reproduksi pada Siswa Siswi di MTSN 01 Kendari - Hartati Bahar; Nabila Rezky Amalia; Nur Indriyani; Putri Gizka Gauzalia; Sri Rahayu; Sri Tandi Gala; Widya Sartika (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
The issue of adolescent reproductive health remains a major challenge in Indonesia, significantly impacting the future of the younger generation. Research by the Indonesian Child Protection Commission (KPAI) and the Ministry of Health in October 2020 indicated that approximately 62.7% of Indonesian adolescents had engaged in premarital sexual relations, with 20% of 94,270 out-of-wedlock pregnancies occurring in adolescent girls, and 21% of these resulting in abortion. This study aimed to enhance MTsN 01 Kendari students with knowledge about the importance of reproductive health, and to measure their knowledge levels through pre-post questionnaire distribution using educational media. The research employed a Pre-Experimental design with a One Group Pre-test - Post-test Design. The study population consisted of 7th-grade students from MTsN 01 Kendari, with a sample size of 35 individuals selected using purposive sampling. Data collection involved questionnaires administered to respondents before and after the educational intervention. The study results showed that the education significantly improved students' knowledge of reproductive health. Based on the pre-test results, 31 (88.57%) students were in the